On the Hermeneuticus I as a Presupposition of Ethical Hermeneutics - Luiz Rohden (Ethic@: an International Journal for Moral Philosophy)
The goal of this paper is to ground the concept of hermeneuticus I based on Hans-Georg Gadamer’s philosophy. Just as we can speak of a Cartesian I or Humean I, I intend to justify the existence of a hermeneuticus I by highlighting one’s posture (Tugend) towards the others. Although neither Gadamer nor his interpreters have coined or discussed this concept from the point of view of ethics, I think it is possible to do so according to the assumption that our peculiar way of being is understanding. In this way, I intend to begin paving the way for the construction of a Hermeneutical Ethics. I propose to do this based on the well-known I-Thou triadic relationship developed by Gadamer in Truth and Method I. Initially, I describe the posture of the two Is and show that their way of relating with the Thou is not hermeneutic. Then, according to Gadamer, I present the third type of I-Thou relationship by systematizing seven ethical postures proper to the hermeneuticus I, which are founded upon the I’s exercise of putting himself or herself in the place of the other, without the intention of instrumentalizing the latter. Finally, I develop conclusions and ethical and sociopolitical implications resulting from the action (praxis) of the hermeneuticus I.